Implementasi Kebijakan Peraturan Pemerintah Nomor 17 Tahun 2020 Tentang Perubahan Atas Peraturan Pemerintah Nomor 11 Tahun 2017 Tentang Manajemen Pegawai Negeri Sipil Dalam Pengembangan Karier Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kota Padangsidimpuan - Nasution, Ikhwan; Isnaini, Isnaini; Lubis, Maksum Syahri (Mahesa Research Center, 2022)
This study aims to explain how to implement Government Regulation Policy Number 17, 2020 concerning Amendments to Government Regulation Number 11, 2017 concerning Management of Civil Servants in Career Development at the Civil Service and Human Resources Development Agency of Padangsidimpuan. This research is designed as a qualitativeresearch with a phenomenological approach that requires researchers to examine a number of subjects by being directly involved and in a relatively long time in order to develop patterns and relationships of meaning. The results of this study looking for four dimensions: first, from the communication dimension that explains the education and training that personality improvement and the inculcation of the spirit of devotion in accordance with the results of the study. Second, from the dimension of resource availability, it is also important in order to carry out Career Development well. Third, for the Disposition dimension regarding the availability of implementers to carry out these public policies, skills alone are not sufficient, without the availability and commitment to implement policies. Fourth, for the dimensions of the Bureaucratic Structure explained that the mutations of BKPSDM employees who experienced it partially felt that they were in accordance with their competencies.